Kinerja Hotel dari Perspektif Balanced Scorecard - Kartika, Erawati (Jurnal Ilmiah Aset, 2009)
From the result of the survey conducted it seem that one of famous hotel which have good image in Malang has not conducted an evolution of comprehensive performance when it seen from the perspective of Balanced Scorecard (BSC), because it only focuses on financial performance. A company needs a type of planning which can create the future of the company through the changes happening recently. Balanced Scorecard is one of new method used is case study method. The object researched is Hotel X in Malang. And the objectives is to know the hotel performance if it is evaluated using BSC quality, they are 1) Increasing the quality of planning significantly, and 2). Increasing the quality of the management of personel performance. The result of the research shows that the performance of hotel X, when it is evaluated using BSC method still needs improvement in the four perspectives is of BSC and for increasing the performance of hotel X, the alternative choosen is to improve the management of personel performance in the frame BSC.